ISOLATED MUSICAL OBSESSIONS - Pfizer, N. (Medknow Publications, 1999)
Musical obsessions are rare in both clinical practice and literature. A case is presented of a musical obsession which had the additional unique characteristics of acute onset, marked severity, and occurrence as an isolated symptom.